Mothers' Views from Underprivileged Families in Preventing School Dropout Rates in Surabaya during Pandemic - Ridwan, Arfiyan; Ridwan, Asrifia (Universitas Mathla'ul Anwar Banten, 2023)
During the covid-19 pandemic, mothers have essential roles in the children’s education process. The online learning system makes mothers, as teachers and parents, provide learning assistance so that children do not drop out of school. A long time before the pandemic, the Local Government of Surabaya had a mentoring program to reduce the dropout rate. However, the program was suspended indefinitely during the covid-19 pandemic. This research aimed to identify mothers' views from underprivileged families in providing learning assistance during the covid-19 pandemic, which was usually carried out by mentoring volunteers before. This research design was descriptive qualitative with data collection techniques conducted in the form of interviews and documentation. Then, the collected data were analyzed using Creswell's hierarchical linear model. The results showed that mothers experienced various difficulties assisting children without a mentoring program from the Local Government of Surabaya. Busyness as career women and the lack of education from the mothers have the potential for children to be vulnerable to dropping out of school. Heretofore, mothers' involvement in alleviating the problem of dropping out of school has received little attention from the Government. Therefore, hopefully, this research contribution can provide the required information in family-based education services improvement during an emergency due to the outbreak.